PENINGKATAN KOMPETENSI PENDIDIK PADA JENJANG PENDIDIKAN ANAK USIA DINI - Laily Hidayati (Al Hikmah: Jurnal Studi Keislaman, 2015)
In several studies on the important role of educators or teachers in the process of socialization and development of the child, Good & Brophy, 2007; Linney & Seidman, 1989 stated that, "a competence teacher is one who is committed to work, is an effective classroom manager, is a positive role model with whom student can identify, is enthusiastic and warm, continuous effort for self-improvement in teaching, possesses skills in human relationship, and can adapt his or her skill to a specific context ". There was also a study done by Brophy, 1992, outlining that "the most powerful socializing influence of the school lies in those who translate program goals into action, the teacher". Also, as stated by by Kohl, 1984 that "children learn best from teachers who are role models, who loves learning". The three descriptions of the important role of educators in the socialization and development of the child above are similar to what was found by Schickedanz, 1990 in his research that "teacher's verbal styles have been found to have an impact on the development of language skill in pre-school children". At this point, it is very important to always make efforts to increase the competence of educators at every level of education, in this case in early childhood education.